Design and analysis an C curved photovoltaic panel - Mhd Saad, Nor Afidah (2024)
Solar power is a kind of renewable energy generated by solar panels. Solar panels harness the energy produced by the sun. Several studies are being conducted to explore how solar panels enhance efficiency. It is crucial since increased efficiency would lead to a reduction in power costs. Due to the current rise in electricity tariffs, solar panels have become quite beneficial to us. However, altering the design of a solar panel may also impact its ability to capture solar radiation, increasing its efficiency. Adding a C curved form to the final design may enhance its visual appeal, making it more intriguing. Various techniques may be used to improve the C curved shape of a solar panel to get a better design. The mathematical algorithm may aid in designing a favorable curvature. The equation for calculating the smooth curvature may be derived using the curve bezier function. The Bezier curve function comprises two circles defined by four key points. This research also investigates the methodology for generating the curve of this function using Solidworks. Solidworks is a 3D CAD that offers comprehensive 2D and 3D solutions for product development, including design, engineering, analysis, and tools for product data management. The software is well-recognized for its intuitive interface and has the trust of a large and diverse user community, which includes engineers, designers, students, and professionals. It also provides capabilities for simulations, visualizations, and collaboration. Solidworks is widely used across several industries for product design and development. Two software applications were used to analyze the new design of the C curved photovoltaic panel. First, the simulation expresses use for linear static analysis, and second, the ANSYS Workbench is used for steady-state thermal analysis. Both analyses were used to evaluate performance on the new design C curved panel. The linear static analysis to assess the structural design, such as Von Mises stress, displacement, and strain, and check the minimum safety factor proceed to the second analysis. The thermal analysis focuses only on computing the electrical conversion efficiency using a fluid-solid interface. It is important to note that the simulation concept differs from fluid-structure interaction. However, the research may be expanded to include additional factors that may lead to high temperatures in the future since it is necessary to conduct a thorough thermal management study to enhance the efficiency and lifespan of new solar panels.